THE INHIBITED CONDITIONS IN THE DRAFT REGULATION OF SURABAYA MAYOR ABOUT THE PROCEDURE OF CHOOSING THE MANAGEMENT OF COMMUNITY EMPOWERMENT OF VILLAGE INSTITUTION, CITIZEN ASSOCIATION AND NEIGHBORHOOD ASSOCIATION - Michael, Tomy (Jurnal Hukum Magnum Opus, 2019)
A person in legal studies can be referred to as a legal subject because he commits the rights and obligations relating to certain matters. As in the early part of Surabaya mayor's draft regulation about the procedures of choosing the Board of Community Empowerment Institution of Local Village Village Institution, Citizen Association and the Neighborhood Association (draft regulation of surabaya’s mayor) that in order to regulate the relationship between Surabaya government with Community Empowerment Institution (LPMK), Citizen Association (RW and the Neighborhood Association (RT) as partners in the implementation of development in the city of Surabaya, the government of Surabaya has established the Mayor’s regulation No. 38 year 2016 on implementation of the Surabaya City Regulation number 15 year 2003 about the guidelines for forming the organization of resilience community of Kelurahan Institutions, RW and RT who are about to organize the electoral ordinances Management of LPMK, RW and RT. The draft of Surabaya’s Mayor regulation before it was confirmed was conducted socialization by the law of the secretariat of Surabaya area in Surabaya on 19 March 2019. This activity has been in accordance with Act No. 12-2011 where the socialization of the first to know the aspirations of the public in this case stakeholders related to the draft Perwali Surabaya. Article 21 of Act No. 25-2009 shows the purpose of a legal state relating to the so-called task of managing and organizing tasks. Related to the government in the modern state, Spelt and ten Berge, distinguishes them in the tasks of regulating and managing the tasks (ordenende en verzorgende taken).